CRYODESMO-O1: A prospective, open phase II study of cryoablation in desmoid tumour patients progressing after medical treatment. (January 2021) - Kurtz, Jean-Emmanuel; Buy, Xavier; Deschamps, Frédéric; Sauleau, Erik; Bouhamama, Amine; Toulmonde, Maud; Honoré, Charles; Bertucci, François; Brahmi, Mehdi; Chevreau, Christine; Duffaud, Florence; Gantzer, Justine; et al.
Abstract: Background: Desmoid tumours (DTs) are rare tumours originating from musculoaponeurotic structures. Although benign, they may be locally aggressive, leading to pain and disability. European Society for Medical Oncology (ESMO) guidelines recommend frontline watchful waiting and medical treatment in progressing tumours. Cryoablation is an interventional radiology technique that is suitable for DT patients (pts) on the basis of repeated cycles of freezing, leading to cell death. Methods: CRYODESMO-01 (ClinicalTrials.gov Identifier: NCT02476305 ) is a prospective, open-label, non-randomised, non-comparative, multicenter study assessing cryoablation in non-abdominopelvic progressing DT. Inclusion criteria were: pts ≥18 y.o., confirmed DT accessible to cryoablation (≥90% destruction), measurable lesion conforming to modified response evaluation criteria in solid tumours (mRECIST), progressive disease after ≥2 lines of medical therapy or with functional symptoms/pain, adequate biological parameters, informed consent, and affiliation to a medical insurance scheme. The primary end-point was the non-progression rate at 12 months; secondary end-points included safety, quality of life (QoL), assessment of pain and functional status. Findings: 50 pts were enrolled (78% female) from four French centres and all were treated. The mean age was 41 y.o. (19–73). The median number of prior treatments was 2.00 [1–4] including non-steroidal anti-inflammatory drugs (NSAIDs), hormone therapy, chemotherapy, and anti-angiogenics. Tumour location included limbs (36%), trunk (60%), and cervical area (4%). The median tumour largest diameter was 89 mm. The rate of non-progressing disease at +12 months was 86% [confidence level (CI) 95% 73–94%]. Median PFS was not reached at a median follow-up of 31 months. Grade 1 and 2 toxicity occurred in 32.8% and 44.5% of patients, grade 3–4 in 22% and no Grade 5 toxicity was observed. Cryoablation significantly improved functional status and pain scores. Interpretation: Cryoablation demonstrated feasibility in progressive DT pts. The study met is primary end-point with 86% of non-progressive disease at +12 months, with reduced pain, better functional status, and encouraging long-term disease control. Highlights: CRYODESMO-01 was the first prospective trial of cryoablation in desmoid tumours. Cryoablation is feasible in progressing, extra-abdominal desmoid tumours. A 86% tumour control was achieved at +12 months. Cryoablation has benefits in terms of pain and quality of life.